The idea of justice - Sen, Amartya, 1933- (London : Allen Lane ; Penguin Books, 2009)
"Is justice an ideal, forever beyond our grasp, or something that may actually guide our practical decisions and enhance our lives? Sen presents an alternative approach to mainstream theories of justice, which, despite their many specific achievements, have taken us, he argues, in the wrong direction in general. One of the principal differences between Sen and the dominant contemporary theorists of justice is that they have been concerned primarily, sometimes wholly, with identifying what perfectly just social arrangements might be, rather than clarifying how different realizations of justice might be compared and evaluated." "At the heart of Sen<U+2019>s argument is his insistence on the role of public reason in establishing what can make societies less unjust. But it is in the nature of reasoning about justice, argues Sen, that it does not allow all questions to be settled even in theory; there are choices to be faced between alterative assessments of what is reasonable; several different and competing positions can each be well defended. Far from rejecting such pluralities or trying to reduce them beyond the limits of reasoning, we should make use of them to construct a theory of justice that can absorb divergent points of view. Sen also shows how concern about the principles of justice in the modern world must avoid parochialism and, further, address questions of global injustice."
Introduction: an approach to justice -- Part I. The Demands of Justice -- 1. Reason and objectivity -- 2. Rawls and beyond -- 3. Institutions and persons -- 4. Voice and social choice -- 5. Impartiality and objectivity -- 6. Closed and open impartiality -- Part II. Forms of Reasoning -- 7. Position, relevance and illusion -- 8. Rationality and other people -- 9. Plurality of impartial reasons -- 10. Realizations, consequences and agency -- Part III. The Materials of Justice -- 11. Lives, freedoms and capabilities -- 12. Capabilities and resources -- 13. Happiness, well-being and capabilities -- 14. Equality and liberty -- Part IV. Public Reasoning and Democracy -- 15. Democracy as public reason -- 16. The practice of democracy -- 17. Human rights and global imperatives -- 18. Justice and the world.
Includes bibliographical notes and indexes.
Refugee Studies Unit (RSU), CPJ
Keywords: Social justice -- Philosophy; Justice, Administration of -- Moral and ethical aspects; Civil rights -- Philosophy; Human rights -- Philosophy; Social ethics